Natriuretic peptide biomarkers in the imminent development of preeclampsia - Marek-Iannucci, Stefanie; Oliveros, Estefania; Brailovsky, Yevgeniy; Pirlamarla, Preethi; Roman, Amanda; Rajapreyar, Indranee N. (Frontiers in Cardiovascular Medicine, 2023)
Preeclampsia is the most common cause of morbidity and mortality in pregnancy, the incidence being significantly higher in low-income countries with reduced access to health care. Women with preeclampsia are at a higher risk of developing cardiovascular disease with a poorer long-term outcome. Early recognition and treatment are key to improving short- and long-term outcomes. Approximately 3%–5% of pregnant women will develop preeclampsia, with potentially fatal outcomes. Despite ongoing research, the exact pathophysiologic mechanism behind its development remains unclear. In this brief report, we describe the potential role of natriuretic peptides as biomarkers in the imminent development of preeclampsia. In a retrospective manner, we analyzed changes in the left ventricular ejection fraction and left atrial volume and increases in natriuretic peptide in correlation with the development of preeclampsia. We found that three out of four patients developed a significant increase in natriuretic peptide, which correlated with the development of preeclampsia and/or peripartum cardiomyopathy. Significant increases in natriuretic peptides around the time of delivery might be a marker for the imminent development of preeclampsia. Close monitoring of natriuretic peptide levels in the peripartum period could give important insight into the imminent development of preeclampsia in high-risk patients. Close follow-up in specialized cardio-obstetric clinics is highly recommended.